A frame shift due to a two‐nucleotide insertion results in the an HLA‐B null allele, B*39:97N. (2nd November 2016) - Wang, W.; Zhang, W.; He, J.; Xu, J.; Zhu, F.‐M.
Abstract : HLA‐B*39:97N differs from HLA‐B*39:01:01 by a two nucleotide insertion at position 604–605.